Utilization of manure and green organic composts as alternative fertilizers for cauliflower production - Simarmata, M.; Susanti, L.; Setyowati, N. (International Journal of Agricultural Technology, 2016)
Cauliflower (Brassica oleraceavar. botrytis) is a vegetablecrop which isgrown over the world. Cultural practices of vegetables production are always dealing with fertilization technologies either using mineral fertilizers, organic fertilizers, or a combination of mineral and organic fertilizers. This study was aimed to determine the effect of reduced the dose of mineral fertilizers and substituted by organic fertilizers from compost ofcow manure and compost of trailing-daisy weeds (Wedelia trilobata).A single factorevaluated was arranged in a completely randomized design (CRD) as follows: treatment of a mineral fertilizer with nitrogen, phosphate, and potassium applied at10, 20 and 30 days after planting at arecommended dose (T1), compost of trailing-daisy weedsat 20 ton ha-1 (T2), compost of cow manure at 20 ton ha-1(T3), 50% of T1 + compost of trailing-daisy weedsat 20 ton ha-1 (T4), 50% of T1 + compost of trailing-daisy weedsat 10 ton ha-1(T5), 50% of T1 + compost of cow manure at20 ton ha-1 (T6), 50% of T1+ compost of cow manure of 10 ton ha-1 (T7), and without fertilizer as a control (T0). Each treatment was repeated five times so that overall there were 40 plantsin40 polybags. The results showed that thefertilizer combinationswere significantly affectedplant height, shoot fresh weight, dry weight of total plant biomass,and curd yield of cauliflower. The highest plant height and shoot fresh weight were observed in the treatment of 50% of mineral fertilizers combined with compost of trailing-daisy weeds at 10 ton ha-1 (T5), the highest of total dry weight of plants were observed in the treatment of cow manure compost (T3), and the highest curd yield of cauliflowerswas observed inthe treatment of 50% of mineral fertilizers combined with cow manure compostat 20 ton ha-1(T6). In conclusion, organic fertilizers from compost of trailing-daisy weeds (Wedelia trilobata) and from cowmanure can be used as an alternative fertilizer to substitutemineral fertilizers on the cauliflower production.